Vantagem competitiva no mercado de geração distribuída de energia solar fotovoltaica - Marcolino, Rodrigo Teixeira (2016)
The market for distributed generation of solar PV is yet in an early stage of development in Brazil. The recent regulatory environment, however, points to a change in this scenario: the latest revisions of the applicable regulation brought increased economic feasibility of projects in the sector. This, along with the presence of abundant solar resource in Brazil and the present stage of development of PV technology indicate a possible increase in the penetration of the source in the country in the coming years. In this context, this study aims to analyze which resources and capabilities the company Axis Renováveis must have to achieve a competitive advantage position, through the RBT lenses. The company that was selected for this single-case study is a start-up in the sector. It is expected that, at the end of the work, the conclusions have direct implications on the company's strategy and can serve as a starting point for others in the industry.